PERANAN KEBIJAKAN PUBLIK TERHADAP PEMELIHARAAN JALAN UMUM - Sudiyarti Sudiyarti (Prodi Ilmu Administrasi Negara, 2018)
This research is willing to know how to overcome the broken roads in East Kalimantan.There are some roads those are very bad it is,therefore to make same traffic accidents.The location of the research is in Samarinda, East Kalimantan in January 2017 from January to April 2017.The method of the research ia by observing the roads :M.Yamin, Kemakmuran,Sebatik and Juanda.The results of the research are that the conditions of the roads in January to April 2017 are very bad among are :(1).On Jalan M.Yamin there are some holes in front of the Mulawarman University’s gate,(2). Kemakmuran there is a broken spot near the Cuture centre service,(3).Sebatik the is a long and dee hole near the BNI 46 office bank,(4).And Juanda there are many holes around the flyover street.The suggestions of the researher are (1).The government has to repair those roads soon,(2).The Government has to put the signs of danger in the broken spot of the street,(3).The Gvernment has to make planning to arrange the repairment,(4).The user of the roads has to be more careful t ride the cycles.